Strategy News Is Good News: How Journalistic Coverage of Politics Reduces Affective Polarization. (3rd September 2021) - Zoizner, Alon; Shenhav, Shaul R.; Fogel-Dror, Yair; Sheafer, Tamir
ABSTRACT: What role does news content play in explaining inter-party hostility? We argue that affective polarization is influenced by exposure to one of the most dominant ways to cover politics: strategy coverage. While previous studies have pointed to the negative consequences of covering politicians' strategies and campaign tactics, we find that this reporting style decreases out-party hostility. Our findings are based on two separate studies: (1) a survey experiment and (2) a cross-sectional analysis that increases external validity by combining survey data with computational content analysis of the articles respondents were exposed to by their primary news sources throughout the 2016 US presidential campaign (415, 604 articles from 157 American news outlets). The results demonstrate that despite the wide criticism of the tendency of journalists to focus on political strategies, such coverage may ease inter-party tensions in American politics.